Pengaruh Penerapan Undang-Undang ITE Terhadap Tingkat Kejahatan Siber Di Indonesia - Aldi ferdiansyah; Berdi Adityas Wiryawan Wahyono; Almansyah Harahap; Evan Gustian; Dzakwan Zaidan (CV. ITTC INDONESIA, 2025)
This study aims to examine the impact of the implementation of the Electronic Information and Transactions Law (UU ITE) on the level of cybercrime in Indonesia. The background of this research highlights that the rapid digital transformation has significantly altered societal interactions while simultaneously creating opportunities for the growth of cybercrimes, such as ransomware attacks, phishing, and personal data theft. This research employs an empirical-normative approach through a literature review and a comparative analysis of cybercrime data before and after the implementation of UU ITE. The study involves an in-depth examination of legal sources, government reports, and case studies to identify challenges in regulatory enforcement and the shortcomings of digital security systems. Findings indicate that while UU ITE provides a clear legal framework, gaps in its implementation have been exploited by cybercriminals to evade legal repercussions. The assessment of regulatory effectiveness emphasizes that strengthening law enforcement capacity and enhancing information technology infrastructure are crucial aspects in reducing cybercrime rates. This study offers policy recommendations for refining digital regulations and improving inter-agency coordination in addressing cyber threats